Experimental Evolution of Campylobacter jejuni Leads to Loss of Motility, rpoN (σ54) Deletion and Genome Reduction - Sher, Azam A.; Jerome, John P.; Bell, Julia A.; Yu, Julian; Kim, Hahyung Y.; Barrick, Jeffrey E.; Mansfield, Linda S. (Frontiers in Microbiology, 2020)
Evolution experiments in the laboratory have focused heavily on model organisms, often to the exclusion of clinically relevant pathogens. The food borne bacterial pathogen Campylobacter jejuni belongs to a genus whose genomes are small compared to those of its closest genomic relative the free-living genus Sulfurospirillum suggesting genome reduction during the course of evolution to host association. C. jejuni serially passaged in rich medium in the laboratory exhibited loss of flagellar motility—an essential function for host colonization. At early time points the motility defect was often reversible, but after 35 days of serial culture, motility was irreversibly lost in most cells in 5 independently evolved populations. Population re-sequencing revealed numerous disruptive mutations to genes in the flagellar transcriptional cascade, including genes affecting the expression of rpoN (σ54) and therefore the expression of the genes σ54 regulates, coupled with deletion of rpoN in all evolved lines. Additional mutations were detected in virulence-related loci. Furthermore, we demonstrate that a phase variable (reversible) motility mutant carrying an adenine deletion within a homopolymeric tract resulting in truncation of the flagellar biosynthesis gene fliR was deficient for colonization in a C57BL/6 IL-10-/- mouse disease model. Re-insertion of an adenine residue partially restored motility and the ability to colonize mice. Thus, a pathogenic C. jejuni strain was rapidly attenuated by experimental laboratory evolution and demonstrated genomic instability during this evolutionary process. The changes observed suggest C. jejuni is able to evolve in a novel environment through genome reduction as well as transition, transversion, and slip-strand mutations.